1977
DOI: 10.1080/03015521.1977.10425933
|View full text |Cite
|
Sign up to set email alerts
|

Glycoalkaloid levels in New Zealand potatoes

Abstract: Tuber glycoalkaloids {TGA) in seven New Zealand potato culti vars were assessed before and after a period of exposure to light. Differences between cultivars were marked, TG.A. concentration ranging from 2.5 to 47.5 mg/100 g fresh weight, Ranking of cultivars was similar before and after exposure. Immature tubers had a higher initial TGA content than mature tubers and accumulated more TGA over the period of exposure. In 'Ham Hardy' tubers, TGA increased most rapidly during the first 20 days. TGA from potato tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Although statistical analysis of results shows cultivar differences in TGA content, because of likely variable recoveries, too much significance cannot be attached to these differences. However, the order of ranking of cuItivars for TGA content is similar at each analysis, and Whitu is consistently lower than Ham Hardy and Rua, which agrees with the findings of Patchett et al (1977). Workers in other countries have found that average TGA levels are in the range 2-13 mg/IOO g whole tuber (Bomer & Mattis 1924;Sinden & Webb 1972), and 20 mg/IOO g is often taken as the maximum acceptable level (Whitaker & Feeney 1973).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Although statistical analysis of results shows cultivar differences in TGA content, because of likely variable recoveries, too much significance cannot be attached to these differences. However, the order of ranking of cuItivars for TGA content is similar at each analysis, and Whitu is consistently lower than Ham Hardy and Rua, which agrees with the findings of Patchett et al (1977). Workers in other countries have found that average TGA levels are in the range 2-13 mg/IOO g whole tuber (Bomer & Mattis 1924;Sinden & Webb 1972), and 20 mg/IOO g is often taken as the maximum acceptable level (Whitaker & Feeney 1973).…”
Section: Resultssupporting
confidence: 69%
“…As already mentioned the ranking of cultivars for TG A content is similar both before and after illumination. Others (Sanford & Sinden 1972;Patchett et al 1977) have found that cultivars with high initial levels tend to accumulate more TGA on exposure to light than those with low initial levels. .…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, early potatoes (i.e., Dark Red Norland) that tend to be smaller would likely have higher TGA at harvest than later varieties grown full season that tend to produce larger tubers 42. The life cycle of the potato is of importance, because tubers susceptible to sprouting have a higher solanine content than freshly harvested tubers 100. Sprouting itself leads to a rise in the solanine content 101, 102.…”
Section: Factors Influencing the Formation Of Ga In Potatoesmentioning
confidence: 99%
“…These steroidal glycoalkaloids (SGA) are natural toxins commonly present in potato varieties in concentrations of up to 100mg/kg (Sinden & Webb, 1974 ;Patchett et al ., 1977 ;Ross et al ., 1978 ;Parnell et al ., 1984 ; Van Gelder, 1985a ;Lammerink, 1985) . In this paper, contents are expressed as mg/kg fresh unpeeled tuber, unless otherwise stated .…”
Section: Introductionmentioning
confidence: 99%
“…Lepper (1949) regarded contents of 150 mg/kg too high for consumption, while McMillan & Thompson (1979) associated a content of 250-300 mg/kg peeled boiled potato with solanine poisoning in schoolboys . Reviews on the toxicology, pharmacology and teratology of steroidal alkaloids (SA) and SGA are given by McMillan & weather during the growing season, and inadequate storage conditions may considerably increase the contents of solanidine glycosides (Bomer & Mattis, 1924 ;Sinden & Webb, 1974 ;Patchett et al ., 1977 ;Ahmed & Miiller,1981 ;Jadhav et al ., 1981) . In Sweden, large amounts of the variety Magnum Bonum had to be withdrawn from commerce recently, because of incidences of illness caused by high levels of solanidine glycosides (Norberg, 1987) .…”
Section: Introductionmentioning
confidence: 99%